Enhancing cancer-supportive care through virtual reality: a policy brief - Esmaeel Toni; Haleh Ayatollahi (Health Research Policy and Systems)
Abstract Background Virtual reality (VR) technology has been useful in enhancing cancer-supportive care by alleviating pain, anxiety and emotional distress. However, its integration into oncology faces multiple barriers, including limited funding, insufficient clinician training, accessibility challenges, absence of standard guidelines and reimbursement policies. This policy brief highlighted policy options needed for VR technology interventions in cancer-supportive care. Methods This policy brief was developed upon a previous systematic review that examined the role of VR in cancer-supportive care. To translate these findings into actionable recommendations, we conducted a secondary analysis of policy-related opportunities and challenges. The extracted evidence was synthesized to propose strategic policy options that facilitate VR adoption in oncology. Results A total of five key policy options were identified: (1) increasing funding for VR research and development, (2) training programs for healthcare professionals, (3) expanding patient access through financial support mechanisms, (4) establishing standard clinical guidelines and (5) developing reimbursement policies. These recommendations aim to bridge the gap between technological advancements and their practical implementation in cancer care. Conclusions Integrating VR into cancer-supportive care requires a coordinated effort among policymakers, healthcare institutions and technology developers. By implementing these evidence-based policy strategies, stakeholders can enhance patient access, improve clinical outcomes and ensure sustainable adoption of VR in oncology.